Effectiveness of Hemodialysis with hemoperfusion as a therapeutic modality in pediatric chronic kidney disease - Ahmedz Widiasta; Rini Rossanti; Dedi Rachmadi; Dany Hilmanto (Medicinski glasnik, 2025)
Introduction: Children receiving regular kidney replacement therapy frequently encounter a state of heightened inflammation, which is evident through symptoms like loss of appetite and elevated levels of ?-2 microglobulin (B2M) in their bloodstream. This loss of appetite leads to a reduction in muscle mass, which, on a biochemical level, can result in diminished cardiac function in these patients. Aim: This research aimed to assess the reduction of inflammation by examining ferritin and B2M serum levels in children with ESKD who are receiving a combination of hemodialysis and hemoperfusion (HDHP). Methods: This research was a retrospective cohort study that utilized data from medical records, focusing on children with CKD who received hemodialysis between January 2020 and December 2022. Pediatric patients undergoing hemodialysis routinely have their nutritional status and appetite assessed. If a patient exhibits reduced food intake and appetite, a B2M serum test is warranted. An elevated B2M level in patients indicates the need for hemodialysis-hemoperfusion (HDHP). Prior to each procedure, including HDHP and blood sampling, informed consent was obtained from both the patients and their legal guardians. Results: HDHP significantly reduces urea, ferritin, and B2M levels in children with ESKD, their decrease are statistically significant with p-value < 0.001. There was a weak positive correlation between ferritin and B2M levels, with a correlation coefficient of 0.195 (95% confidence interval [CI]: 0.003-1.000) and p = 0.043. This finding suggests that increased ferritin levels are associated with significantly increased B2M levels. Conclusion: HDHP leads to a significant reduction in urea, ferritin, and B2M levels in children with ESKD, with these decreases being statistically significant, as indicated by a p-value of less than 0.001. A weak positive correlation was observed between ferritin and B2M levels, with a correlation coefficient of 0.195 (95% confidence interval [CI]: 0.003-1.000) and a p-value of 0.043. This result implies that higher ferritin levels are linked to a notable increase in B2M levels. Keywords: Children, cardiovascular, chronic kidney disease, hemodialysis, hemoperfusion
Keywords: children; cardiovascular; chronic kidney disease; hemodialysis; hemoperfusion